Aerosol generation during routine rhinologic surgeries and in‐office procedures. Issue 1 (14th January 2021) - Sharma, Dhruv; Campiti, Vincent J.; Ye, Michael J.; Rubel, Kolin E.; Higgins, Thomas S.; Wu, Arthur W.; Shipchandler, Taha Z.; Burgin, Sarah J.; Sim, Michael W.; Illing, Elisa A.; Park, Jae Hong; Ting, Jonathan Y.
Abstract: Objective: Cadaveric simulations have shown endonasal drilling and cautery generate aerosols, which is a significant concern for otolaryngologists during the COVID‐19 era. This study quantifies aerosol generation during routine rhinologic surgeries and in‐office procedures in live patients. Methods: Aerosols ranging from 0.30 to 10.0 μm were measured in real‐time using an optical particle sizer during surgeries and in‐office procedures. Various mask conditions were tested during rigid nasal endoscopy (RNE) and postoperative debridement (POD). Results: Higher aerosol concentrations (AC) ranging from 2.69 to 10.0 μm were measured during RNE ( n = 9) with no mask vs two mask conditions ( P = .002 and P = .017). Mean AC (0.30‐10.0 μm) were significantly higher during POD (n = 9) for no mask vs a mask covering the patient's mouth condition (mean difference = 0.16 ± 0.03 particles/cm 3, 95% CI 0.10‐0.22, P < .001). There were no discernible spikes in aerosol levels during endoscopic septoplasty (n = 3). Aerosol spikes were measured in two of three functional endoscopic sinus surgeries (FESS) with microdebrider. Using suction mitigation, there were no discernible spikes during powered drilling in two anterior skull base surgeries (ASBS). Conclusion: Use of a surgical mask over the patient's mouth during in‐office procedures or a mask with a slit for an endoscope during RNE significantly diminished aerosol generation. However, whether this reduction in aerosol generation is sufficient to prevent transmission of communicable diseases via aerosols was beyond the scope of this study. There were several spikes in aerosols during FESS and ASBS, though none were associated with endonasal drilling with the use of suction mitigation. Level of Evidence: 4. Abstract :